Meningkatkan Kemandirian Siswa Melalui Pendampingan Wirausaha Home Industri Tempe: Sebuah Pendekatan Pendidikan Praktis - Maftuhah, Maftuhah (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2025)
One of the big problems that is often experienced by our society at this time is the problem of unemployment which is increasing day by day. This occurs due to an imbalance between population and available jobs. However, when viewed from a different perspective, each individual can create employment opportunities provided that they have the potential to create regional economic independence. This work-based KKN service provides training to students by practicing skills in making tempeh. This soybean product is in great demand and popular in the market, besides that it has a high nutritional content and an affordable price. Based on the results of observations and interviews, the participants participated in the activities enthusiastically and enthusiastically. This activity makes students start to consider starting a business so they can earn additional income. It is hoped that with this training students can increase their potential in entrepreneurship